The PINS Trial: a prospective randomized clinical trial comparing a traditional versus an emollient skincare regimen for the care of pin-sites in patients with circular frames. (1st February 2021) - Ferguson, David; Harwood, Paul; Allgar, Victoria; Roy, Anu; Foster, Patrick; Taylor, Martin; Moulder, Elizabeth; Sharma, Hemant
Abstract : Aims: Pin-site infection remains a significant problem for patients treated by external fixation. A randomized trial was undertaken to compare the weekly use of alcoholic chlorhexidine (CHX) for pin-site care with an emollient skin preparation in patients with a tibial fracture treated with a circular frame. Methods: Patients were randomized to use either 0.5% CHX or Dermol (DML) 500 emollient pin-site care. A skin biopsy was taken from the tibia during surgery to measure the dermal and epidermal thickness and capillary, macrophage, and T-cell counts per high-powered field. The pH and hydration of the skin were measured preoperatively, at follow-up, and if pin-site infection occurred. Pin-site infection was defined using a validated clinical system. Results: Out of 116 patients who were enrolled in the study, 23 patients (40%) in the CHX group and 26 (44%) in the DML group had at least one bad or ugly pin-site infection. This difference was not statistically significant (p = 0.71). There was no significant relationship between pH or hydration of the skin and pin-site infection. The epidermal thickness was found to be significantly greater in patients who had a pin-site infection compared with those who did not (p = 0.01). Skin irritation requiring a change of treatment occurred in four patients (7%) using CHX, and none using DML. Conclusion: We found no significant difference in the incidence of pin-site infection between the CHX and DML treatment groups. Dermol appeared to offer a small but significant advantage in terms of tolerability. We did not find a significant association between patient or treatment related factors and pin-site infection. It is therefore difficult to make specific recommendations based upon these results. The use of either cleaning agent appears to be appropriate. Cite this article: Bone Joint J 2021;103-B(2):279–285.